Role-Playing Center as a Space for Social Development and Self-Expression of Early Childhood Through Educational Play Tools at the FG Kindergarten Lab, Faculty of Teacher Training and Education, University of Riau - Tesa Amelia; Siti Nurfadilah; Sonia Rahmi Junita; Rika Fitri Ramadani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine the utilization of Educational Play Tools (APE) in the role-play center in supporting the development of social interaction and self-expression in early childhood at TK-FG Lab FKIP UNRI. This study employed a qualitative descriptive method through observation, documentation, and in-depth interviews with center teachers. The results show that the APE used in the role-play center, such as profession props, kitchen utensils, and planting media, are able to encourage children to interact actively, develop both verbal and nonverbal communication, and express their emotions and imagination within meaningful thematic contexts. The class rotation system implemented every two days also contributes to broadening children's social experiences across different groups. This study confirms that the role-play center supported by theme-appropriate APE serves as an effective learning space for the development of social interaction and self-expression in early childhood.